Perancangan Aplikasi Monitoring Produksi pada Perusahaan yang Memproduksi Acrylic - Nilo Legowo; I Made Kresna Yoga (Bina Nusantara University, 2012)
A lot of problems often occur in production monitoring, because companies still rely on manual processing system. Therefore, this research is objected to facilitate the monitoring of production processes, to minimize human error in the production process, to make automatic the process of existing transactions, toclarify the duties of production monitoring of an acrylic manufacturer. The research methodology used is literature study by reviewing previous theories and studies related to the topic. Furthermore, analysis method by studying the running system of the company as well as evaluating the distributed questionnaire and analyzing the results. And finally is the design method using the Object-Oriented with UML. The research resulted in an application design of a production monitoring system. The result of this design has been implemented into the selected DBMS. The new monitoring system helps monitoring the production system properly, as well as makes the transaction run systematically. The each production process starting from project orders, sample orders, sales orders, material releases, production, assembly, and delivery order within can be monitored quickly and properly. The activity reports can also be generated more systematically and comprehensibly.